Long‐term mark‐and‐recapture study of a freshwater mussel reveals patterns of habitat use and an association between survival and river discharge. (9th May 2014) - Inoue, Kentaro; Levine, Todd D.; Lang, Brian K.; Berg, David J.
Summary Climate change and human population growth threaten the supply of fresh water for human use and freshwater biodiversity. Long‐term studies are necessary to identify the effects of such temporal trends on biological and ecological phenomena; however, the collection of long‐term data can be costly and time‐consuming. We investigated the effect of hydrological variation over time on population dynamics in a perennial river of the northern Chihuahuan Desert, using an imperilled freshwater mussel (Popenaias popeii) as a model. We conducted a 15‐year mark‐and‐recapture study, and distance sampling, to estimate demographic parameters while accounting for habitat heterogeneity and changes in river discharge. Recapture probability varied between microhabitats, and survival was positively correlated with river discharge. Survival and the finite rate of population growth were relatively stable over time. Over 60% of individuals were found at relatively high density in riffle habitats, which compose c. 16% of the total study area. Mean monthly temperature in the region increased over the past 100 years, and mean monthly discharge of the Black River declined over the past 65 years. With no significant trends in total monthly precipitation, declines in discharge suggest that reduction of stream flow is likely due to lowering of the water table and decreased groundwater recharge. Significant changes in climate and hydrological regimes, and increases in anthropogenic threats (increased water demand, degraded water quality) in the region, may induce significant declines in population size of this imperilled mussel. We demonstrated the importance of considering habitat heterogeneity and hydrological cycles over time to examine population dynamics. Survival of benthic invertebrates in desert streams is sensitive to hydrological cycles, which are expected to be altered via climate change and extensive water use. Species recovery plans need to incorporate knowledge of spatial distributions when designing strategies for habitat assessment and making conservation decisions.